Methods of Water Removal From Liquid Epoxy Resin - Popardovská Eva; Popardovský Vladimír; Danko Ján (Journal of Mechanical Engineering)
The aim of the article is to show the possibilities of releasing water from liquid epoxy resin. It is important to perform this procedure with the resin that is to be used for the lamination process. Water-contaminated resin negatively affects the polymerization process of epoxy resin and has an adverse impact on the mechanical properties of the resulting laminate. This article describes two methods of releasing water from resin. The water content in the resin was measured spectrometrically (NIR spectrometry)